Northern Shrimp (Pandalus borealis) on Flemish Cap in July-August 1997 - Río-Iglesias, José Luis del (1997)
A stratified random bottom-trawl surveys on Flemish Cap was carried out in July-August 1997 following the same method used since 1988. Results of shrimp population (Pandalus borealis) are presented in this paper and compared with those previously observed.